Hubungan Pekerjaan Orang Tua Dengan Stimulasi Dini Pada Anak Usia 0-36 Bulan diwilayah Kerja Puskesmas Bungo I Kabupaten Bungo - Suhaela Arofah; Citra Indah Fitriwati (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
The stages of development that must be passed by children, including language development, gross motor, fine motor and social. Cognitive and language disorders account for about 8% of developmental disorders in children caused by stimulation or parental communication patterns. Working mothers can have a positive or negative impact on child development. Based on data from the Central Bureau of Statistics, from 100% of women in Indonesia, 97.25% are working women, the remaining 2.74% women do not work.Objective: To determine the relationship between parents' work and early stimulation in children aged 0-36 months.The cross sectional research design is a form of non-experimental observational study research that is descriptive.Results: The group of parents who do not work as many as 13 people (73.9%), the group of parents who work as many as 6 people (26.1%). The respondent group received early stimulation as many as 14 people (60.9%), the respondent group did not get early stimulation 9 people (39.1%). The relationship between the variables of parents' work and early stimulation is that parents who do not work do not do early stimulation as many as 4 people and parents do not work to do early stimulation as many as 13 people. The job status of parents who work and do not do early stimulation is 2 people, doing early stimulation is 4 people.Conclusion: There is no relationship between maternal employment status with early stimulation,through the chi square statistical test p = 0.510. Keywords: Toddler, Working Mother, Early Stimulation